Trade Liberalisation and Pitfalls to Nigeria’s Effective Participation in Global Trade - mohammed, ngozi thelma; Mijah, Etham B (Advances in Social Sciences Research Journal, 2015)
Globalisation is no longer new on the block. However, scholars are still interested in studying the effects of its aftershocks in the areas of trade, politics and socio-cultural remits in international relations. Conceived and promoted by neo-liberal think-tanks and institutions as the magic wand to socio-economic problems across the globe irrespective of the peculiar challenges of less developed countries compared to the much developed ones, it has turn out to be the exact opposite of the globalization philosophy. This paper examines the globalization philosophy as is affects Nigeria in its bid to actively participates in the global trade as one of the core tenents of a globalised space. It argued that the globalised space is imbued with a lot of asymmetries to the disadvantage of Nigeria to equitably participate in global trade. At best, the paper concludes that under the present circumstances, Nigeria will remain a dependent partner in the globalised equation, unless some remedial measures are taken to harness opportunities available to enhance her marginal participation in the globalised market space.